2001
DOI: 10.1021/bp000159f
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Antiagglomeration Effect of a Yeast Biosurfactant, Diacylmannosylerythritol, on Ice‐Water Slurry for Cold Thermal Storage

Abstract: Antiagglomeration effects of different surfactants on ice slurry formation were examined to improve the efficiency of an ice-water slurry system to be used for cold thermal storage. Among the chemical surfactants tested, a nonionic surfactant, poly(oxyethylene) sorbitan dioleate, was found to show a greater antiagglomeration effect on the slurry than anionic, cationic, or amphoteric surfactants. More interestingly, diacylmannosylerythritol, a glycolipid biosurfactant produced by a yeast strain of Candida antar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…They can be used in the treatment of schizophrenia or diseases caused by dopamine metabolic dysfunction [67,72] and microbial infections [37]. MELs are used in the puriWcation of lectins (Immunoglobulin G) [9,15,16,21,39] and in the preparation of ice-slurry as an antiagglomeration agent [41,42]. Self-assembling properties [17-20, 39, 43, 70] of MELs are of recent interest because this behavior could be leveraged in gene transfection and drug delivery [23,24,42,43,65,66].…”
Section: Mel: Why?mentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used in the treatment of schizophrenia or diseases caused by dopamine metabolic dysfunction [67,72] and microbial infections [37]. MELs are used in the puriWcation of lectins (Immunoglobulin G) [9,15,16,21,39] and in the preparation of ice-slurry as an antiagglomeration agent [41,42]. Self-assembling properties [17-20, 39, 43, 70] of MELs are of recent interest because this behavior could be leveraged in gene transfection and drug delivery [23,24,42,43,65,66].…”
Section: Mel: Why?mentioning
confidence: 99%
“…BSs form complex (chelate) with heavy metals including Cd 2+ , Pb 2+ , Zn 2+ and Hg 2+ and hence reduce their toxicity [13,52,58]. They act as carbon and energy storage molecules and remain as a protective layer for the microorganisms against the environment with high ionic strength [41,42,58]. BSs may be the byproducts released in response to the environmental changes and may have a role in DNA transfer in natural environment, since they can enhance gene uptake via transfection [13,23,24,58,61].…”
Section: Introductionmentioning
confidence: 99%
“…They can be used in the treatment of schizophrenia or diseases caused by dopamine metabolic dysfunction (Vertesy et al 2002;Zhao et al 2000) and microbial infections (Kitamoto et al 1993b). MELs are used in the purification of lectins (Immunoglobulin G) (Kitamoto et al 2000;Im et al 2001Im et al , 2003Imura et al 2007b;) and in the preparation of ice-slurry, as an antiagglomeration agent (Kitamoto et al 2001b(Kitamoto et al , 2002. In addition, MEL-A, acetylated at C-4 and/or C-6, markedly increases the efficiency of gene transfection mediated by cationic liposomes (Inoh et al 2001(Inoh et al , 2004.…”
Section: Significance Of Melmentioning
confidence: 99%
“…MEL at low concentration (10 mg/L) gets adsorbed on the ice surface and suppresses this agglomeration process. Their effective performance has also been tested successfully in a large-scale model (300 L) (Inaba 2000;Kitamoto et al 2000Kitamoto et al , 2001b.…”
Section: Inhibition Of Ice Agglomerationmentioning
confidence: 99%
“…They also induce cell differentiation in the human leukemia cells [40], rat pheochromocytoma cells [42], and mouse melanoma cells [43]. In addition, it was recently demonstrated that MEL act as potential anti-agglomeration agents in an ice-water slurry system to be used for cold thermal storage [44]. Alkanes ranging from C 12 to C 18 were converted into glycolipid biosurfactants 34 ± 36 by resting cells of Pseudozyma (Candida) antarctica T-34 [45].…”
Section: Formation Of Fatty Acid Glucuronides 16 ± 18 In Human Livermentioning
confidence: 99%